MENINGKATKAN MINAT BELAJAR KITAB SUCI PADA SISWA KELAS X SMA KATOLIK BHAKTI LUHUR MALANG - Alan Ketmoen (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
This study aims to increase students’ interest in learning the Holy Scriptures among tenth-grade students of Bhakti Luhur Catholic Senior High School Malang through interactive and contextual learning methods. This research was motivated by the low interest of students in participating in Holy Scripture learning due to monotonous and less engaging teaching methods. Therefore, a learning assistance program using a participatory approach was conducted to encourage students to become more active and interested in understanding the Holy Scriptures. The research method used was descriptive qualitative through observation, interviews, and learning assistance activities. The stages of the research included observing students’ conditions, identifying problems, and implementing learning activities through group discussions, reflections, and audiovisual media. The novelty of this study lies in the use of a contextual approach that connects the Holy Scriptures with students’ daily life experiences. The results showed that students became more active, enthusiastic, and more interested in reading and understanding the Holy Scriptures. In addition, a communicative and creative learning atmosphere helped increase students’ learning motivation, making Holy Scripture learning more enjoyable and meaningful.